Effect of pelvic floor muscle training combined with hydrotherapy on postoperative rehabilitation of patients undergoing for sphincter preservation rectal cancer (盆底肌锻炼联合水疗促进直肠癌患者保肛术后康复效果研究) - HUANG Liming (黄丽明); WU Lifang (吴丽芳) (中西医结合护理)
Objective To investigate the effect of pelvic floor muscle training combined with hydrotherapy on postoperative rehabilitation of patients undergoing for sphincter preservation rectal cancer. Methods Totally 66 patients undergoing for sphincter preservation rectal cancer were randomly divided into the control group and observation group, with 33 cases in each group. All patients received routine supportive treatment and nursing, and those in the observation group were given pelvic floor muscle training combined with hydrotherapy for 6 months. The degree of low anterior resection syndrome(LARS)and incontinence dermatitis were measured and compared between two groups. Results There were 9 (27. 27%)patients with mild to severe LARS in the observation group and 20 (60. 61%)patients with mild to severe LARS in the control group at 6 month after operation(P＜0. 05). The incidence of incontinence dermatitis in the observation group was lower than that in the control group(P＜0. 01). Conclusion The pelvic floor muscle training combined with hydrotherapy is potentially effective to improve the postoperative defecation, reduce the risk of incontinence dermatitis and improve the quality of life among patients undergoing for sphincter preservation rectal cancer. (目的 探讨盆底肌锻炼联合水疗促进中低位直肠癌患者保肛术后康复的效果。方法 选取66例中低位直肠癌行保肛手术的患者为研究对象。采用随机数字表法将66例患者分成观察组和对照组。对照组采用一般支持性治疗, 观察组在对照组基础上进行为期6个月的盆底肌锻炼联合水疗法。采用低位前切除综合征(LARS)工具、失禁性皮炎评估工具评估患者的LARS、失禁性皮炎程度, 评价康复效果。结果 术后6个月, 轻重度LARS观察组出现9(27. 27%)例, 低于对照组的20(60. 61%)例, 差异有统计学意义(P＜0. 05); 观察组术后失禁性皮炎发生率低于对照组, 差异有统计学意义(P＜0. 01)。结论 盆底肌锻炼联合水疗能有效改善患者排便功能, 降低失禁性皮炎发生率, 提高生活质量, 值得借鉴。)